2020
DOI: 10.1111/jcpp.13329
|View full text |Cite
|
Sign up to set email alerts
|

Behavior in childhood is associated with romantic partnering patterns in adulthood

Abstract: Background: Most people will partner at some point during their lives. Yet little is known about the association between childhood behavior and patterns of long-term romantic partnering in adulthood. Methods: In this population-based cohort study, behavioral ratings were prospectively obtained from teachers when children (n = 2,960) were aged 10-12 yearsfor inattention, hyperactivity, aggression-opposition, anxiety, and prosocialityand linked to their tax return records from age 18 to 35 years (1998)(1999)(200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…The study by Vergunst et al has multiple strengths: (a) the use of multi‐informant data, childhood behaviors were rated by teachers whereas partnership data at the ages 18–35 were derived from tax return records; (b) adequate controls of background characteristics (gender of child and family socio‐economic status), and (c) a big sample size allowing to assess adequately heterogeneity of partnering trajectories. The report also adds to the growing but relatively small number of studies demonstrate that childhood behaviors are predictive of adult behavior (for instance Pingault et al, 2011 ; Rivenbark et al, 2018, as cited in Vergunst et al, 2020 ; Vergunst, Tremblay, Nagin, Algan, et al, 2019 ; Vergunst, Tremblay, Nagin, Zheng, et al, 2019 ). A limitation of this type of studies is that they identify earlier markers of adult problems but are not informative on the developmental processes that carry their effects.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…The study by Vergunst et al has multiple strengths: (a) the use of multi‐informant data, childhood behaviors were rated by teachers whereas partnership data at the ages 18–35 were derived from tax return records; (b) adequate controls of background characteristics (gender of child and family socio‐economic status), and (c) a big sample size allowing to assess adequately heterogeneity of partnering trajectories. The report also adds to the growing but relatively small number of studies demonstrate that childhood behaviors are predictive of adult behavior (for instance Pingault et al, 2011 ; Rivenbark et al, 2018, as cited in Vergunst et al, 2020 ; Vergunst, Tremblay, Nagin, Algan, et al, 2019 ; Vergunst, Tremblay, Nagin, Zheng, et al, 2019 ). A limitation of this type of studies is that they identify earlier markers of adult problems but are not informative on the developmental processes that carry their effects.…”
mentioning
confidence: 75%
“…Taken together, these findings suggest that effects of family adversity and individual traits (inattention and aggression-opposition) on the increased likelihood of following the early-partnered-separated trajectory could disappear after inclusion of parentadolescent relationships in the study's design. Vergunst et al (2020) show that family adversity in childhood is predictive of problems in formation and maintenance of intimate relationships in the next generation. Similarly, Pingault et al showed that low parental educational and occupational level predicted lower educational attainment in the next generation, Vergunst, Tremblay, Nagin, Algan, et al (2019) that low parental educational and occupational level predicted lower income in the next generation, and Vergunst, Tremblay, Nagin, Zheng, et al (2019) that low parental income predicted more reliance on governmental financial support in the next generation.…”
Section: Formation and Maintenance Of Intimate Relationshipsmentioning
confidence: 97%
See 3 more Smart Citations